Effect of defensive pressure on movement behaviour during an under-18 basketball game - Leite, N. M.; Leser, R.; Gonçalves, B.; Calleja-Gonzalez, J.; Baca, A.; Sampaio, J. (International Journal of Sports Medicine, 2014)
The aim of this study was to examine the effect of defensive pressure on movement behaviour during an under-18 basketball game. 20 international male players (age: M=16.05, SD=2.09 years old; weekly practice: M=10.9, SD=1.94 h; playing experience: M=7.1, SD=1.1 years) played two 10-min basketball quarters, using man-to-man ¼-court for the first 4 min (F¼), man-to-man full court defence for the next 3 min (FULL), and man-to-man ¼-court defence for the last 3 min (S¼). The positional data were captured by the Ubisense Real Time Location System and analysed with non-linear signal processing methods (approximate entropy) and repeated measures ANOVA. There were differences in the regularity values between F¼ and FULL in distance to the basket and to the opponents` basket. A stronger in-phase attraction in both lateral and longitudinal directions was identified; however, the centroids (i. e., the mean position from all team players) were closer and revealed higher values of irregularity in lateral displacements for all defensive systems. The individual speed displacements became more coordinated with teammates, particularly in the offensive court. Overall, this study provided evidence on how changing the level of defensive pressure promotes different collective behaviours.